Economic growth of Mizoram : role of business and industry - Kabra, K.C. (New Delhi, 2008)
This book attempts to examine the role of business and industry in the economic growth of the state of Mizoram. Tracing the factors that led to the development of business and industry in the state, it analyzes the role of government in the promotion and regulation of business and industry. It also extends an elaborate discussion on the role played by financial institutions and public sector undertakings (PSUs) in the development of industry in Mizoram, the taxation policies, and the problems faced by the business and industry in the state.
Keywords: Industrial policy - India - Mizoram - History